INCIDENCE AND DIVERSITY SPECTRUM OF MITOSPORIC FUNGI FROM THE COLD ARID BASE SOIL OF MOONLAND LANDSCAPE (LADAKH), INDIA. - SKARMA NONZOM,; GEETA SUMBALI, (International Journal of Pharma and Bio Sciences, 2015)
The cold deserts of Ladakh region present extreme environmental challenges for microorganisms in the form of subzero temperatures due to prolonged snow cover, lack of appropriate moisture during summers, high altitude and high UV radiations. In view of these prevailing conditions, a study was undertaken to assess the diversity of mitosporic fungi found in the cold arid base soil of Moonland landscape, Ladakh (J&K). This was done by using dilution plate technique and modified Czapek Dox Agar medium (CDA). A total of 32 fungal species belonging to 14 genera were recovered from the four sites of sampling and majorities (64%) of them were found to be melanized. The fungal species of common occurrence included Alternaria alternata, Aspergillus flavus, A. fumigatus, A. ochraceous A. sydowii, A. niger, Cladosporium cladosporiodes, C. sphaerospermum, C.oxysporum, Penicillium griseofulvum, P. olivicolor, P. italicum, P. verrucosum and Ulocladium atrum. Diversity indices viz., species richness (S), Shannon-Wiener’s diversity index (H') and Simpson Dominance index (Cd) were also considered. Their values for (H') and (Cd) did not differ significantly in the investigated four sites but (S) values varied with the sites.